Recent advances in Moringa oleifera supplementation for maternal anemia and infant nutrition: A systematic review - Hadjo, Daniel Ariel; Lada, Christina Olly; Mozez, Itrin Diana (Indonesian Nutrition Association, 2025)
Moringa oleifera (MO) is a plant-based food source that lasts during certain seasons, and some societies still consider it to be known as superfood. The use of MO has been linked up to its inconsistency and advances as a supplementation in resolving maternal anemia and stunted infants. This study aims to synthesize an updated efficacy and safety aspect of MO supplementation in pregnant women and infants.